Synthesis of donor-acceptor substituted oligothiophenes by Stille coupling - Raposo, M. Manuela M. (2004)
A synthesis of donor-acceptor-substituted oligothiophenes by Stille coupling is described. The 5´-estanyl derivatives, readily prepared from 5-alkoxy- and 5-amino-2,2´-bithiophenes 7 were coupled with the appropriate aryl or heteroaryl bromides to give the title compounds.